Saccharomyces cerevisiae responds similarly to co‐culture or to a fraction enriched in Metschnikowia pulcherrima extracellular vesicles. Issue 5 (25th February 2023) - Mejias‐Ortiz, Miguel; Mencher, Ana; Morales, Pilar; Tronchoni, Jordi; Gonzalez, Ramon
Abstract: The recent introduction of non‐conventional yeast species as companion wine starters has prompted a growing interest in microbial interactions during wine fermentation. There is evidence of interactions through interference and exploitation competition, as well as interactions depending on physical contact. Furthermore, the results of some transcriptomic analyses suggest interspecific communication, but the molecules or biological structures involved in recognition are not well understood. In this work, we explored extracellular vesicles (EVs) as possible mediators of interspecific communication between wine yeasts. The transcriptomic response of Saccharomyces cerevisiae after 3 h of contact with a fraction enriched in EVs of Metschnikowia pulcherrima was compared with that induced by active M . pulcherrima cells. Interestingly, there is a high level of overlap between the transcriptomic profiles of yeast cells challenged by either M . pulcherrima whole cells or the EV‐enriched fraction. The results indicate an upregulation of yeast metabolism in response to competing species (in line with previous results). This finding points to the presence of a signal, in the EV‐enriched fraction, that can be perceived by the yeast cells as a cue for the presence of competitors, even in the absence of metabolically active cells of the other species. Abstract : Saccharomyces cerevisiae accelerates transcription of genes involved in energy metabolism and growth; and inhibits autophagy in response to extracellular vesicles (EVs) of Metschnikowia pulcherrima . This response emulates closely to that to whole cells of the competing yeast species. This suggests EVs might be part of the signal informing S . cerevisiae of the presence of competing yeasts.